Perancangan Desain Kaos Sebagai Visual Merchandise di PT. Urban Spasial Indonesia - Zebrinna Delivia Putri Bahri; Alfian Candra Ayuswantana (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Â In the case of application creativity in the domain of design industry, t-shirt design is regarded as one of the creative forms in the industry, evolving beyond simple clothing and functionality, according to a case study on the application of creativity in the field of design industry. The T-shirt design process at PT. Urban Spasial Indonesia, a consulting firm that specializes in mapping and spatial planning, is the subject of this study. This design is visually appealing and consistent with the company's brand identity thanks to the use of graphic design. At PT. Urban Spasial Indonesia, achieving balance between innovation, brand identity, creativity, and trend sensitivity is essential. A case study approach is used in conjunction with qualitative research methodology. This study clarifies that, especially in T-shirt design, typography, visual coherence, and adaptation to the target audience are essential elements for any design layout. Furthermore, the study delves deeply into the creative, tactical, and useful concepts that underpin T-shirt design.